Online retail for a sustainable tomorrow - Sharifuddin, Shafinas; Misaridin, Nur Aulia Fahada; Wan Abu Bakar, Wan Hashridz Rizali (Journal of Islamic, Social, Economics and Development, 2025)
As worldwide awareness of environmental concerns grows, customers are looking for more sustainable choices, with a focus on environmentally friendly items. The rise of e-commerce has accelerated this trend, giving customers easy access to a wide range of items, including those with environmentally friendly features. However, online purchases of green products might decline due to a variety of circumstances. Thus, the article examines crucial aspects influencing customer behaviour while purchasing green items online. Drawing on an integrated analysis of current research, the study identifies and analyses five critical aspects that influence customers' decisions to purchase environmentally friendly items in the online marketplace. These components include environmental awareness, eco-labelling, green advertising, attitudes, and trust. The study demonstrates that these characteristics not only have an individual influence on green product purchases, but also define the distinct landscape of online green product buying. The intricate interaction of these factors is investigated, emphasising their importance in the larger context of sustainable consumption, and offering insight on developing patterns in consumer behaviour online. The findings offer useful information for companies, legislators, and academics looking to improve sustainable practices in the digital marketplace and further our knowledge of the complex dynamics underlying the online purchase of green products.